Understanding Organizational Leadership - Mark A. Brennan; M. K. Moon; Dale Pracht (EDIS)
FCS-9262, a 4-page fact sheet by M.A. Brennan, M.K. Moon, and Dale Pracht, is part of a series of discussions on the connection between citizen leadership capacities and successful community development. It introduces the concept of organizational leadership and describes organizational leadership styles. Includes references. Published by the UF Department of Family Youth and Community Sciences, September 2008. Reviewed January 2009.